Epigenome‐Wide Study of Posttraumatic Stress Disorder Symptom Severity in a Treatment‐Seeking Adolescent Sample. Issue 3 (2nd February 2021) - Sheerin, Christina M.; Lancaster, Eva E.; York, Timothy P.; Walker, Jesse; Danielson, Carla Kmett; Amstadter, Ananda B.
Abstract: Emerging research has demonstrated that psychosocial trauma exposure may elicit epigenetic changes, with downstream effects on the transcriptional regulation of genes. Epigenome‐wide association studies (EWAS) offer an agnostic approach to examine DNA methylation (DNAm) associations and are a valuable tool to aid in the identification of biological pathways involved in posttraumatic stress disorder (PTSD). This study represents the first EWAS of PTSD in an adolescent sample, an important group given the significance of this developmental period regarding both DNAm changes and PTSD risk. The sample ( n = 39, M age = 15.41 years, SD = 1.27, 84.6% female) comprised adolescents who experienced interpersonal trauma and were enrolled in a treatment study. Participants were assessed using the UCLA PTSD Reaction Index for DSM ‐ IV –Adolescent Version and provided a blood sample at baseline. Genomic DNA was isolated from whole blood and assayed using the Illumina Infinium MethylationEPIC BeadChip. The primary analysis estimated the associations among individual CpG sites and PTSD symptom scores. Of the 793, 575 screened probes tested, two were significant at a false discovery rate (FDR) < 10%. Hypomethylation of both sites was associated with increased PTSD symptom scores. Analysis of differentially methylated regions (DMR) identified a DMR associated with PTSD symptom scores at an FDR < 10%. Results from follow‐up models are also discussed. Findings from this preliminary investigation suggest the importance of further research conducted in adolescent samples. The analytic pipeline and results are documented for use in future meta‐analytic work as more such samples become available. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0252.R1_Sheerin‐2021_Cantonese Traditional Chinese 對尋求治療的青少年創傷後壓力症症狀嚴重程度的全基因組研究 摘要: 新興研究表明, 社會心理創傷暴露可能引起表觀遺傳變化, 對基因的轉錄調節產生下游影響。全基因組關聯研究(EWAS)提供了一種不可知的方法來檢查DNA甲基化(DNAm)的關聯, 是一種有價值的工具, 有助於識別參與創傷後壓力症(PTSD)的生物途徑。本研究代表了第一個青少年樣本的創傷後壓力症的EWAS, 鑑於這個發育期對DNAm變化和創傷後壓力症風險的重要性, 這是一個重要群體。樣本(n=39, M年齡=15.41歲, SD=1.27, 84.6%為女性)由經歷過人際關係創傷的青少年組成, 並參加了一項治療研究。參與者使用UCLA DSM‐IV‐青少年版創傷後壓力症反應指數進行評估, 並在基線時提供血樣。從全血中分離出基因組DNA, 用Illumina EPIC 晶片進行檢測。初步分析估計了個體CpG位點和創傷後壓力症症狀得分之間的關聯。有兩個在錯誤發現率(FDR) < 10%的情況下顯著。這兩個部位的低甲基化與創傷後壓力症症狀評分增加有關。對差異甲基化區域(DMR)的分析發現, 在FDR < 10%時, DMR與創傷後壓力症症狀得分相關。對後續模型的結果也進行了討論。這項初步調查的結果表明在青少年樣本中進行進一步研究的重要性。隨著更多此類樣本的出現, 分析管道和結果被記錄下來, 用於未來的元分析工作。 Simplified Chinese 对寻求治疗的青少年创伤后压力症症状严重程度的全基因组研究 摘要: 新兴研究表明, 社会心理创伤暴露可能引起表观遗传变化, 对基因的转录调节产生下游影响。全基因组关联研究(EWAS)提供了一种不可知的方法来检查DNA甲基化(DNAm)的关联, 是一种有价值的工具, 有助于识别参与创伤后压力症(PTSD)的生物途径。本研究代表了第一个青少年样本的创伤后压力症的EWAS, 鉴于这个发育期对DNAm变化和创伤后压力症风险的重要性, 这是一个重要群体。样本(n=39, M年龄=15.41岁, SD=1.27, 84.6%为女性)由经历过人际关系创伤的青少年组成, 并参加了一项治疗研究。参与者使用UCLA DSM‐IV‐青少年版创伤后压力症反应指数进行评估, 并在基线时提供血样。从全血中分离出基因组DNA, 用Illumina EPIC 芯片进行检测。初步分析估计了个体CpG位点和创伤后压力症症状得分之间的关联。有两个在错误发现率(FDR) < 10%的情况下显著。这两个部位的低甲基化与创伤后压力症症状评分增加有关。对差异甲基化区域(DMR)的分析发现, 在FDR < 10%时, DMR与创伤后压力症症状得分相关。对后续模型的结果也进行了讨论。这项初步调查的结果表明在青少年样本中进行进一步研究的重要性。随着更多此类样本的出现, 分析管道和结果被记录下来, 用于未来的元分析工作。